Increased fasting small‐bowel water content in untreated coeliac disease and scleroderma as assessed by magnetic resonance imaging. Issue 10 (1st December 2019) - Lam, Ching; Sanders, David S; Lanyon, Peter; Garsed, Klara; Foley, Stephen; Pritchard, Susan; Marciani, Luca; Hoad, Caroline L; Costigan, Carolyn; Gowland, Penny; Spiller, Robin
Abstract : Background and aims: The regular overnight migrating motor complex (MMC) ensures that the normal fasting small‐bowel water content (SBWC) is minimised. We have applied our recently validated non‐invasive magnetic resonance technique to assess SBWC in newly diagnosed coeliac disease (CD), scleroderma (SCD) and irritable bowel syndrome (IBS), conditions possibly associated with small intestinal bacterial overgrowth (SIBO). Methods: A total of 20 CD and 15 SCD patients with gastrointestinal symptoms were compared to 20 healthy volunteers (HV) and 26 IBS with diarrhoea (IBS‐D) patients, as previously reported. All underwent a fasting magnetic resonance imaging (MRI) scan on a 1.5 T Philips Achieva MRI scanner to assess fasting SBWC and colonic volumes. Stool and symptom diaries were completed for one week. Results: Compared to HV, all patients had significantly increased stool frequency and Bristol stool form score. SBWC was significantly increased in CD (median 109 mL; interquartile range (IQR) 53–224 mL) compared to HV (median 53 mL; IQR 31–98 mL; p < 0.01) and IBS‐D (median 42 mL; IQR 28–67 mL; p < 0.01). A variable increase in SBWC was also found in SCD (median 77 mL; IQR 39–158 mL), but this was not significant ( p = 0.2). Colonic volumes were similar for all groups, being a median of 547 mL (IQR 442–786 mL) for CD, 511 mL (453–789 mL) for SCD, 612 mL (445–746 mL) for HV and 521 mL (428–757 mL) for IBS‐D. When CD patients were subdivided according to the Marsh classification, the higher grades had larger colonic volumes. Conclusion: Fasting SBWC as assessed by MRI is significantly increased in newly diagnosed CD and SCD but decreased in IBS‐D. Future studies should test whether increased resting fluid predisposes to SIBO.